Wounding enhances expression of AtSUC3, a sucrose transporter from Arabidopsis sieve elements and sink tissues. - Meyer, Stefan; Lauterbach, Christian; Niedermeier, Matthias; Barth, Inga; Sauer, Norbert; et al. (Plant Physiology, 2004)
The Arabidopsis AtSUC3 gene encodes a sucrose (Suc) transporter that differs in size and intron number from all other Arabidopsis Suc transport proteins. Each plant species analyzed so far possesses one transporter of this special type, and several functions have been discussed for these proteins, including the catalysis of transmembrane Suc transport, and also Suc sensing and regulation of other Suc transporters. Here, we show that the AtSUC3 protein is localized in the sieve elements of the Arabidopsis phloem and is not colocalized with the companion cell-specific AtSUC2 phloem loader. Even stronger AtSUC3 expression is observed in numerous sink cells and tissues, such as guard cells, trichomes, germinating pollen, root tips, the developing seed coat, or stipules. Moreover, AtSUC3 expression is strongly induced upon wounding of Arabidopsis tissue. The physiological role of AtSUC3 in these different cells and tissues is discussed.